First Description of a Primitive Neuroectodermal Tumor Arising in the Nose. (22nd May 2013) - Rizk, Habib; Khazzaka, Aline; Sebaaly, Amer; Cherfan, Maguy; Tomb, Roland; Sarkis, Riad
Abstract : We report the case of a 12-year-old girl, who consulted us with one-year history of an 8 mm nose lesion that was painless and firm upon palpation. The lesion was resected conservatively. Immunohistochemistry was in favor of a primitive neuroectodermal tumor (PNET)/Ewing's sarcoma lesion, excluding epithelial, lymphoid, and other tumors. After a second resection, our patient was referred to chemotherapy and has already undergone 9 cycles out of 14. The patient is to date with no evidence of persistent or recurrent disease. To our knowledge, this is the first description of a PNET arising in the nose.